PREVENTIVE TRAINING PROGRAMME FOR PATIENTS AFTER ACUTE CORONARY EVENT-- CORRELATION BETWEEN SELECTED PARAMETERS AND AGE GROUPS - Vysoký, Robert; Fiala, Jindřich; Dosbaba, Filip; Bat'alik, Ladislav; Nehyba, Svatopluk; Ludka, Ondřej (Central European journal of public health, 2015)
AIM: Interventional cardiovascular training programmes provide a prescription of optimal form and safe intensity. They are part of the second phase of cardiovascular rehabilitation which is a key point in the whole tertiary-preventive care for patients with coronary artery disease. The patients are hemodynamically adapted to a normal physical load, their aerobic capacity is gradually increased, and they learn principles of regular aerobic-resistance exercise. The aim of this study is to assess the impact of modified aerobic-resistance exercise on cardiorespiratory indicators in patients after acute coronary event, and evaluate the differences between monitored parameters in different age groups. METHODS: The study was conducted on a group of 106 patients (85% of men) of an average age of 60.4 ± 10.9 years, with left ventricular ejec- tion fraction of 57.4 ± 7.2%. All subjects went through an acute coronary event. The time elapsed between the occurence of a coronary event and the beginning of the training programme was 35 ± 8 days. In patients after coronary artery bypass grafting, the time passed was 50 ± 16 days on average. All patients received a two-month aerobic-resistance training with a frequency of three times a week. The length of a training unit was set to 100 minutes (out of which 60 minutes were allocated to individual aerobic training). RESULTS: A significant negative correlation between age and average values of monitored parameters was observed. Even though the values of all parameters are decreasing with increasing age, a shift towards higher values in all parameters occurred after completing the training programme. The study reveals that there are interindividual differences between the parameter values. Asignificant difference in individual parameters was found between different age groups. The result of the study shows that a given parameter could characterize each age group. Completing the interventional training programme also led to a significant increase of exercise tolerance (1.8 ± 0.3 vs. 2.0 ± 0.4 W/kg; p < 0.001) and of peak oxygen consumption (22.8 ± 4.5 vs. 25.9 ± 5.5 ml/kg/min, p < 0.001). CONCLUSION: Interindividual differences between the parameter values have been identified. This could be helpful in methodological conception of preventive training programmes for patients suffering from cardiovascular disease. The mutual connection between the parameter values and age groups does not relate only to a safer training intensity determination, but also to a more precisely targeted application of different training modalities in order to achieve an optimal final training effect.
Keywords: Male; Coronary Disease; tělesná výkonnost; koronární nemoc; terapie cvičením; nestabilní angina pectoris; Age Factors; Aged; mužské pohlaví; senioři; lidé; ženské pohlaví; Angina, Unstable; Humans; Exercise Therapy; věkové faktory; Physical Fitness; Female; lidé středního věku; Middle Aged